ASSESSMENT OF FETAL AGE BY MONITORING FETAL GROWTH USING TRANSABDOMINAL ULTRASOUND IN NELLORE EWES - JYOTHI, K; SUDHA, G; KRISHNA, K MOULI; SAHADEV, A; NARAYANSWAMY, M; RAO, SUGUNA; KSHAMA, M A (The Indian Journal of Animal Reproduction, 2023)
Nellore Brown ewes (n=20) were subjected to short day estrus synchronization protocol and transabdominal ultrasonography was conducted weekly once from day 8 onwards until parturition. Pregnancy was determined after observation of fluid accumulation in uterine horns on day 22. The embryo was observed on day 29 in all ewes, head and trunk demarcation, fore and hind limb buds on day 36, heartbeat, umbilical cord, C shaped placentomes on day 43, ossification of vertebral column, rib cage, orbits, long bones of limbs, genital tubercle, rumen, brain ventricles on day 50, the four chambers of heart on day 57, diaphragm, eye lens, stomach chambers, major blood vessels on day 64, Kidneys, liver, urinary bladder, intestinal masses and lungs with bronchi on day 71, the trachea, jugular vein on day 99, the kidneys took bean shape with demarcation of cortex and medulla, placentomes hollowed out with hyperechoic borders and gastric chambers were observed on day 113. The time of organization of embryo, ossification of fetal bones and echogenicity of placentomes might help in judging the fetal age.